Long‐term effectiveness of the preoperative smoking cessation programme at Western Health. Issue 9 (21st July 2017) - Taylor, Hugh; Karahalios, Amalia; Bramley, David
Abstract : Background: Smoking is associated with adverse effects in the perioperative period, including elevated risk of death. The perioperative period provides an opportunity to engage with patients who are smokers to encourage smoking cessation, often referred to as a 'teachable moment'. We developed a smoking intervention model for the pre‐admission clinic (PAC) at Western Health, Victoria, Australia. This case series aimed to assess the impact of the smoking intervention model, which is standard of care, on the participant's smoking habits over four time points. Methods: We enrolled 50 consecutive participants for elective surgery who were smokers and had attended PAC at Western Health, Footscray. All smokers were offered a standard intervention package to address their smoking. Participants underwent a brief interview to elicit their current smoking behaviour on their day of surgery, 3 and 12 months post‐operatively. Results: We found a reduction at each time point post‐intervention in the average number of cigarettes smoked per day by all participants with a 43% reduction at 12 months compared with PAC. We found that the number of participants who had quit increased at each time point, with 29% abstinent at 12 months post‐operatively. At 12 months, we found 71% of participants had either quit or reduced the number of cigarettes smoked compared with the amount reported at PAC. Conclusion: This study adds to the evidence that a simple intervention preoperatively can contribute to long‐term changes in smoking behaviour.